Peningkatan Kesehatan Masyarakat Suku Arfak melalui Bakti Sosial di Kampung Kwau Papua Barat: Improvement of Public Health Arfak Tribe through Social Service in Kwau Village West Papua - Elda Irma Jeanne Joice Kawulur; Keliopas Krey; Sita Ratnawati; Sabarita Sinuraya; Rawati Panjaitan; Yenny Yendri Salosa; Maria Massora; Paskalina Theresia Lefaan; Agatha Cecilia Maturbongs; Wendy Yudija Limbong Allo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Health services in Papua are still a serious problem that not all Papuan people cannot reach, especially people living in remote and mountainous areas. Kampung The purpose of this service activity is to provide free health check up and assess nutritional status in an effort to improve the health of the Arfak community in Kwau Village, West Papua Province. through health checks and body measurements. The number of patients receiving treatment was 85 people with an age range of 1-70 years, consisting of children to elderly patients. Our result showed most of the patients suffered from Acute Respiratory Tract Infection (ARI) as many as 39 people, then stomach ulcers as many as 18 patients, muscle diseases and arthritis as many as 18 people. Other diseases, which amounted to 10 people, were relatively few suffered by the people of Kampung Kwau. In general, children in Kwau Village have good nutrition. There were three children who were categorized as very short. The sustainable use and management of local food by the Arfak traditional community in Kwau Village shows that the community has sufficient food security to meet optimal nutritional intake.